(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The essay discusses the identity and language of three groups which are considered to display hybrid characteristics. These three groups are the Samsams, Baba Nyonya and the Jawi Peranakans. They are predominantly found in the northern part of peninsular Malaysia. As a concept, hybrid refers to the nature of a system which forms a cluster of several subsystems or segments that are different from one another. This hybrid concept is used to explain the identity of the three above groups. Even though the language spoken by the three groups display hybrid characteristics, their linguistic classifications indicate the speech systems of both the Samsams and Jawi Peranakans as dialect, whereas the speech system of the Baba Nyonya as creole. The essay also reviews the linguistic classification of speech systems of these three groups.